Dietary inclusion of Hermetia illucens larvae meal modifies caecal microbiota diversity and composition in barbary partridges (Alectoris barbara) - Atallah, Elie; Mahayri, Tiziana Maria; Mrázek, Jakub; Bovera, Fulvia; Piccolo, Giovanni; Fliegerová, Kateřina Olša; Moniello, Giuseppe (Scientific reports, 2025)
In the present study, we examined the influence of the dietary inclusion of black soldier fly (BSF) larvae meal on the diversity and composition of the bacterial community in the caecum of Barbary partridges (Alectoris barbara). A total of 54 partridges were divided equally into three treatment groups. The control group (C) received a diet containing corn-soybean meals and the two experimental groups received diets in which soybean meal protein was partially substituted with BSF larvae meal at proportions of 25% (H25) and 50% (H50). The bacterial community of the caecal samples was analysed in 30 slaughtered animals (10 per group) at 64 days of age. High-throughput sequencing targeting the V4-V5 region of the 16 S rRNA gene was used. Firmicutes were the most abundant phylum in all studied categories. This phylum was dominated by the families Ruminococcaceae and Lachnospiraceae. The caecal microbiota was significantly altered at the genus level. The linear discriminant analysis effect size (LefSe) analysis for the differential taxa abundance revealed several significant dissimilarities between the control group (C) and the groups with 25% and 50% insect meal replacement, with 13 and 20 taxa with significantly different abundances, respectively. Several of these taxa are associated with gut health, fiber fermentation, and metabolic functions, indicating a biological importance of the observed microbial shifts. Compared with the control group, the partridges fed 25% BSF larvae meal had a significantly higher bacterial phylogenetic abundance and richness, which may contribute to improved gut health and a more stable microbial environment. The beta diversity measures revealed that all three groups of animals were significantly spatially separated. The results demonstrated the significant impact of black soldier fly larvae meal on the caecal microbiota of Barbary partridges. The positive influence of the insect meal used was indicated by increased bacterial diversity in the H25 group and increased relative abundance of several potentially beneficial genera in both experimental groups.
Keywords: RNA ribozomální 16S; Galliformes; Cecum; Gut microbiota; cékum; střevní mikroflóra; Bacteria; larva; krmivo pro zvířata; Black soldier fly; Barbary partridges; Gastrointestinal Microbiome; Animal Feed; RNA, Ribosomal, 16S; dieta; biodiverzita; Insect; Diet; zvířata; Animals; Larva; Diptera; Biodiversity